2010
DOI: 10.1111/j.1750-3841.2010.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclusion of Salmon Roe on Characteristics of Salmon Baby Food Products

Abstract: Baby food was formulated from sockeye salmon (puree alone, puree + chunks, puree + pink row, puree + pink row + chunks, puree + red row, puree + red roe + chunks). In the 1st study, physical (pH, instrumental color, water activity) and descriptive sensory (odor, flavor, texture, visual color) characteristics were determined. Samples containing roe were lighter and less red (by approximately 3 to 4 a* units) than formulations without roe regardless of the type of roe added. Visual pink color followed the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Including roe in the formulation produced a lighter, less red, retort-processed product; while including oil and/or bone produced a darker, redder, retortprocessed product. Similar results for effects of roe on L * and a * values in retort-processed purees have been reported by DeSantos et al (2010b). The retort-processed puree + oil formulation was most yellow, and puree + roe was least yellow.…”
Section: Characteristics Of Retort-processed Materialssupporting
confidence: 89%
See 4 more Smart Citations
“…Including roe in the formulation produced a lighter, less red, retort-processed product; while including oil and/or bone produced a darker, redder, retortprocessed product. Similar results for effects of roe on L * and a * values in retort-processed purees have been reported by DeSantos et al (2010b). The retort-processed puree + oil formulation was most yellow, and puree + roe was least yellow.…”
Section: Characteristics Of Retort-processed Materialssupporting
confidence: 89%
“…Formulations containing puree and puree + roe had similar salmon odor intensities. DeSantos et al (2010b), however, reported that retort-processed salmon puree containing roe had a more intense salmon flavor than puree alone.…”
Section: Sensory Characteristicsmentioning
confidence: 92%
See 3 more Smart Citations